Digitalization of Family Courts through the E-Court System to Ensure Access to Justice in Indonesia - Muhammad Roihan Qowima; Durrul Aulya Anhar (Jurnal Hukum Keluarga, 2026)
Digital transformation in Indonesia’s judicial system through the implementation of e-Court is a strategic step toward realizing the principles of swift, simple, and cost-effective justice. This study aims to analyze the effectiveness of the digitization of family courts and its implications for public access to justice. The research method employed is normative legal research using a doctrinal and statutory approach. Legal sources were obtained through literature review and analysis of legislation, particularly the Law on Information and Electronic Transactions and Supreme Court Regulation No. 7 of 2022 regarding Amendments to Supreme Court Regulation No. 1 of 2019 on Case Administration and Electronic Court Proceedings. The research findings indicate that the e-Court system provides administrative conveniences, such as case registration, payment of case filing fees, and electronic hearings. However, its implementation still faces challenges in the form of the digital divide, low digital literacy, and personal data protection issues. Therefore, regulatory strengthening, infrastructure improvements, and optimized outreach are needed so that the digitization of the judiciary can truly ensure equitable access to justice.